ქართლი და სასანიანთა ირანი III საუკუნეში. რელიგიური ასპექტი - მშვილდაძე/ Mshvildadze, მარიკა/ Marika (ივანე ჯავახიშვილის სახელობის თბილისის სახელმწიფო უნივერსიტეტის გამომცემლობა, 2022)
In the 1st-3rd centuries A.D. Kartli was included in the geopolitical sphere of “Pax Romana”. The exception is middle of the 3rd century A.D., when King Amazasp of Kartli, due to the political situation, was forced to change his state orientation and recognize himself as a vassal of Shah Shabur I of Iran. The 3rd century is an important period for Sassanid Iran, which can be called the era of religious reforms (Kartir and Mani. Zoroastrianism and Manichaeism). Our area of interest is to find out how much the religious situation in Sassanid Iran of the 3rd century reflected on Kartli. The paper examines and analyzes political and religious issues between Iberia and Sasanian Iran based on historical sources and artifacts. The research shows that due to the political situation, Kartli could not bypass the religious processes taking place in Sasanian Iran in the 3rd century, but, at the same time, these processes supposedly had a smaller impact on Kartli. It is noteworthy that Sasanian engraved gems in Kartli appear mostly after the IV century and throughout the Sasanian period. The engraved gems a contemporary historical document on which the depictions of deities, symbols and ritual scenes shed light on the religious beliefs of this or that period. Due to the above, despite the fact that the state orientation towards the east (Sassanid Iran) was changed by the king of Kartli Amazasp, the expansion of Zoroastrianism from Sassanid Iran should not have taken place during the reign of both Amazasp and Rev I the Just (King of Iberia). Due to the geopolitical situation, it is also difficult to imagine the conversion of the kings of Kartli (Amazasp and Rev I the Just) to Manichaean religion, which was not in the interests of either the Roman Empire or Sasanian Iran.
KARTLI AND SASANIAN IRAN IN THE 3RD CENTURY. RELIGIOUS ASPECT
https://geohistory.humanities.tsu.ge/ge/procedings/83-shromebi/177-shromebi-18.html
Keywords: რომაული ზავი; მანიქეველობა; ქართლი